RANCANG BANGUN REACTION TIMER DENGAN KEYPAD DAN PENYIMPAN DATA - Muhammad Ikhwan Ardiansyah (UIN Sunan Kalijaga Yogyakarta, 2018)
Reaction time became one of the discussion in the Work Design Analysis and Ergonomics. Reaction time is used to measure work performance of a worker. A person who reacts quickly when subject to stimulation, indicates that the person has a high performance. Thus the high or low performance of a person is measured on the basis of the quick or slow of a person in reacting to the stimulus. This research will discuss about how to design and build a reaction timer built microcontroller with input in the keypad which equipped with data storage device.